Evaluation of Postoperative Clinical and Radiological Outcomes of Thoracolumbar Vertebral Fractures - Erdinç Acar; Derya Dinçer (Eurasian Journal of Emergency Medicine, 2019)

(untitled)
Aim:The aim of this study was to measure a variety of clinical and radiological outcomes in a group of patients with thoracolumbar fractures who underwent surgery at a single center.Materials and Methods:We retrospectively analyzed 50 consecutive patients who underwent surgery for thoracolumbar vertebral fractures between September 2000 and December 2011. We assessed clinical outcomes with the visual analogue scale (VAS) for pain, Oswestry disability ındex (ODI), and Frankel scale. We measured radiological outcomes using the sagittal index (SI), Local Kyphosis Angle (LKA), and anterior corpus height loss (ACHL).Results:Preoperative, postoperative, and final visit mean VAS values were 82 mm, 60 mm, and 13.5 mm, and mean ODI values were 65%, 40%, and 15%, respectively. These clinical outcome improvements were all statistically significant (p<0.05). Similarly, mean SI values were 20°, 14°, and 15°, mean LKA values were 17°, 9°, and 13°, and mean ACHL values were 45%, 25%, and 28%, respectively. The preoperative to postoperative radiological outcome improvements were all statistically significant (p<0.05), whereas the postoperative to final visit measures actually demonstrated loss of correction, although these changes were not statistically significant.Conclusion:Although major progress has been made in the treatment of thoracolumbar vertebral fractures, the lack of standardized, verified clinical and radiological outcome measures continues to pose a challenge to the accurate assessment of the results of management.